Phytochemical Composition and Biological Activities of Extracts and Essential Oil of the Stem Bark of Pentas schimperiana (A. Rich.) Vatke, and In Silico Molecular Docking and ADMET Study of Selected Compounds from its Essential Oil. - Darwin Demissie (ASTU, 2024)
Medicinal plants play a key role in the healthcare system facilities of local communities as the major parts of medicine mainly in the rural population. Pentas schimperiana is a plant traditionally used in different areas of Africa, including Ethiopia, for the treatment of blackleg, epilepsy, bone fractures, hepatitis B liver infection, diabetes mellitus, livestock mental problems, and calf fattening. This study was aimed to identify antibacterial and antioxidant phytochemicals from the stem bark of Pentas schimperiana. In this study the stem bark of Pentas schimperiana was successively extracted by maceration with petroleum ether (PET), chloroform, and methanol to afford 1.74 g (0.22 %), 6.55 g (0.83 %), and 26.71 g (3.38 %) yields, respectively. Silica gel column chromatographic separation of the extracts afforded four compounds-based TLC profile and their structures were partially characterized by FTIR. The essential oil was extracted by hydro-distillation technique and analyzed by GC-MS. A total number of 29 components were identified. The antibacterial and antioxidant activities were evaluated using agar disc diffusion method against four strains of bacteria and DPPH methods, respectively. All crude extracts displayed promising growth inhibitory effect at the concentration of 200 mg/mL against the E. coli and their zone of inhibition are 20±0.82 mm for MeOH extract, 21.07±0.47 mm for CHCl3 extract and 21.67±0.47mm for PET extract compared to ciprofloxacin (26.17±0.9 mm). The essential oil of Pentas schimperiana stem bark showed good zone of inhibition 15±0.00 mm against E. coli at concentration of 1 mg/mL, followed by inhibition against P. aeruginosa with the zone of inhibition values of 14±1.00 mm. The highest percent inhibition of the DPPH radical was observed with PET extract (IC50: 2.81 μg/mL) compared with ascorbic acid (IC50: 0.5 μg/mL) and also essential oil showed promising inhibitions IC50: 6.63 μg/mL compared with ascorbic acid (IC50: 2.89 μg/mL). Based on highest percentage composition five major compounds namely: butyl 9,12-octadecadienoate (14), linoelaidic acid (15), 9-octadecenoic acid (Z)-, oxiranylmethyl ester (16), oleic acid (17), and β-Monolinolein (18) were selected from essential oil for in silico molecular docking and ADMET study and exhibited good results. The current study revealed that the plant is promising source of antibacterial and antioxidant phytochemicals which support the traditional use of Pentas schimperiana for the treatment of various ailments.
Keywords: Pentas schimperiana, Phytochemicals, Bioactivity, in silico molecular docking, ADMET